"The guys love it when chicks ask for help": an exploration of female rugby league fans. Issue 5 (4th May 2022) - Richards, Jessica; Parry, Keith D.; Gill, Fiona
Abstract: This article explores the relationship between gender, space and performances of fandom by female match-going fans of the Australian rugby league team the St George Illawarra Dragons. Drawing on a case study that utilised participant observation, semi-structured interviews and a focus group, this article develops a fan typology that details four different types of female fans of rugby league. The findings suggest some female fans were under levels of stricter gatekeeping by male fans depending on their spatial location inside of the stadium. Their inclusion into match-day culture was, therefore, shown to have limits. On the one hand, female match-going fans have agency and choice in the construction and interchange of a fan identity, but on the other, that same identity attests to oppression. We conclude that traditional match-day engagement with rugby league requires conformity to a predominantly masculine ideal. Supplemental data for this article is available online at https://doi.org/10.1080/17430437.2020.1809380 .